Photo-controlled exchange bias in CoO@Co–Fe PBA core–shell heterostructures. Issue 1 (7th December 2021) - Yao, Kangkang; Li, Jianing; Yuan, Shuang; Cao, Kaiyan; Wang, Fang; Zhang, Yin; Tian, Fanghua; Wang, Jinwen; Wang, Qiang; Yang, Sen
Abstract : After red irradiation, the exchange bias field of the CoO@Co–Fe PBA hybrid reduces by ∼50%. In addition, the value of H EB can be further regulated accurately by setting the irradiation time or adjusting the incident light frequency. Abstract : Regulating the exchange bias (EB) effect via an external field allows one to effectively tailor the properties of spin-valve-based spintronic devices. However, as a reliable way to manipulate the magnetic properties of materials, there have been few reports on the effect of light irradiation on the EB effect so far. In this work, a non-volatile light-tunable EB effect is achieved in a well-designed CoO and CoFe Prussian blue analogue core–shell structure (CoO@Co–Fe PBA), where the antiferromagnetic CoO has a large anisotropy, and the molecular magnet Co–Fe PBA is photosensitive. The EB field of this hybrid can be reduced by ∼50% after irradiation for 20 minutes, and the photo-induced change can be further increased by extending the irradiation time. In addition, the switching of the two EB effect states can be successfully implemented by switching red and blue light irradiation. Herein, this interesting photo-controlled EB effect is attributed to the change in the magnetization of the photosensitive Co–Fe PBA shell after light radiation, and the change is achieved by manipulating the number of Fe III –Co II magnetic pairs in the shell by incident light. Apparently, this striking light-controlled EB effect opens up new prospects for the design of new-generation optoelectronic devices.